Longitudinal peripheral tissue RNA‐Seq transcriptomic profiling, hyperalgesia, and wound healing in the rat plantar surgical incision model. Issue 10 (9th September 2021) - Goto, Taichi; Sapio, Matthew R.; Maric, Dragan; Robinson, Jeffrey M.; Domenichiello, Anthony F.; Saligan, Leorey N.; Mannes, Andrew J.; Iadarola, Michael J.
Abstract: Postoperative pain and delayed healing in surgical wounds, which require complex management strategies have understudied complicated mechanisms. Here we investigated temporal changes in behavior, tissue structure, and transcriptomic profiles in a rat model of a surgical incision, using hyperalgesic behavioral tests, histological analyses, and next‐generation RNA sequencing, respectively. The most rapidly (1 hour) expressed genes were the chemokines, Cxcl1 and Cxcl2 . Consequently, infiltrating leukocytes were abundantly observed starting at 6 and peaking at 24 hours after incising which was supported by histological analysis and appearance of the neutrophil markers, S100a8 and S100a9 . At this time, hyperalgesia was at a peak and overall transcriptional activity was most highly activated. At the 1‐day timepoint, Nppb, coding for natriuretic peptide precursor B, was the most strongly upregulated gene and was localized by in situ hybridization to the epidermal keratinocytes at the margins of the incision. Nppb was basically unaffected in a peripheral inflammation model transcriptomic dataset. At the late phase of wound healing, five secreted, incision‐specific peptidases, Mmp2, Aebp1, Mmp23, Adamts7, and Adamtsl1, showed increased expression, supporting the idea of a sustained tissue remodeling process. Transcripts that are specifically upregulated at each timepoint in the incision model may be potential candidates for either biomarkers or therapeutic targets for wound pain and wound healing. This study incorporates the examination of longitudinal temporal molecular responses, corresponding anatomical localization, and hyperalgesic behavioral alterations in the surgical incision model that together provide important and novel foundational knowledge to understand mechanisms of wound pain and wound healing.